2017
DOI: 10.1016/j.wneu.2016.12.087
|View full text |Cite
|
Sign up to set email alerts
|

The Extended Lateral Supraorbital Approach and Extradural Anterior Clinoidectomy Through a Frontopterio-Orbital Window: Technical Note and Pilot Surgical Series

Abstract: The extended LSO approach opens a new route (frontopterio-orbital window) to perform extradural anterior clinoidectomy safely and increases surgical exposure, angles, and operability of a less invasive keyhole craniotomy (LSO approach) to treat anterior cranial fossa lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…This means that further frontal lobe retraction is needed to provide sufficient exposure of the surgical target when using the subfrontal corridor, even for approaching the anterior cranial fossa and midline region. 1,9 Moreover, because the dissection of the sylvian fissure is hindered when using an SOa, surgical maneuverability in the middle cranial fossa is also reduced. Some authors have previously shown technical difficulties in approaching middle fossa lesions via an SOa.…”
Section: Discussionmentioning
confidence: 99%
“…This means that further frontal lobe retraction is needed to provide sufficient exposure of the surgical target when using the subfrontal corridor, even for approaching the anterior cranial fossa and midline region. 1,9 Moreover, because the dissection of the sylvian fissure is hindered when using an SOa, surgical maneuverability in the middle cranial fossa is also reduced. Some authors have previously shown technical difficulties in approaching middle fossa lesions via an SOa.…”
Section: Discussionmentioning
confidence: 99%
“…Extradural clinoidectomy allows for a wider bone removal between the optic canal and the superior orbital fissure by providing an easier identification and anatomical orientation than the intradural technique. [24][25][26][27][28][29][30][31][32] With the suspicious of a malignant tumor pathology, one more argument favoring the extradural clinoidectomy is to minimize the possibility of intradural tumor spread. 12 Nonetheless, the long-standing history of the severe visual impairment can explain the lack of any postoperative improvement.…”
Section: Discussionmentioning
confidence: 99%
“… 73 Its use for pituitary adenomas, craniopharyngiomas, and clinoidal and tuberculum sellae meningiomas has been described. 1 2 Approach can be pterional, 74 orbitozygomatic, 37 75 modified pterional, 76 modified orbitozygomatic, 40 pretemporal transzygomatic transcavernous, 39 77 temporopolar epidural transcavernous transpetrous, 78 extended lateral supraorbital, 79 and endoscopic transsphenoidal. 24 …”
Section: Discussionmentioning
confidence: 99%